Development and Validation of Analytical Methodology and Evaluation of the Impact of Culture Conditions and Collection Associated with the Seasonality in the Production of Essential Oil of Plectranthus amboinicus (Lour) Spreng - Carneiro, Fabíola B.; Júnior, Irinaldo D.; Lopes, Pablo Q.; Macêdo, Rui O. (IntechOpen, 2012)
None